2019
DOI: 10.1308/rcsann.2019.0016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gait kinematics in total and unicondylar knee replacement surgery

Abstract: Introduction This study is aimed to compare kinematic gait data of patients who have undergone total and unicondylar knee replacement. Materials and methods This single-surgeon retrospective cohort study evaluated 13 patients with unilateral total knee arthroplasty (TKA) and 14 unicondylar knee arthroplasty (UKA). Gait analysis was carried out using a Vicon motion analysis system. The limits of knee flexion during stance phase, at heel strike and at loading response were measured. Results The total range of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
(23 reference statements)
0
15
1
Order By: Relevance
“…Despite this wide variability, which is diagnostic criteria dependent, POUR is a significant concern for patients and health-care providers. Not only is an overdistended bladder and subsequent catheterization uncomfortable for the patient, but it may also increase the risk of urinary tract infections (UTIs) and delay mobilization [ 11 , 12 ], both of which may impede same-day discharge, leading to increased health-care costs. In the postoperative orthopedic setting, UTIs may undergo hematogenous seeding [ 13 ], which can lead to periprosthetic joint infections.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this wide variability, which is diagnostic criteria dependent, POUR is a significant concern for patients and health-care providers. Not only is an overdistended bladder and subsequent catheterization uncomfortable for the patient, but it may also increase the risk of urinary tract infections (UTIs) and delay mobilization [ 11 , 12 ], both of which may impede same-day discharge, leading to increased health-care costs. In the postoperative orthopedic setting, UTIs may undergo hematogenous seeding [ 13 ], which can lead to periprosthetic joint infections.…”
Section: Introductionmentioning
confidence: 99%
“…2 Patients with increased extensor strength report better outcomes, 40 however TKA is known to reduce extensor strength relative to native knees, 41 , 42 impacting gait and other functional activities. PKA has been associated with restoration of kinematics and gait toward that of the native knee, 17 improved range of motion, and faster return to desired physical function. 5 The improved function of PKA is, in part, a consequence of retention of the anterior cruciate ligament (ACL), which is otherwise sacrificed for nearly all TKA designs.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with functional cruciate ligaments, and disease isolated to one tibiofemoral knee compartment, the use of unicompartmental knee arthroplasty (UKA) instead of TKA can lead to improved patient satisfaction and knee function, with reported benefits including faster gait, greater range of motion, and earlier return to desired activity. 7 , 17 - 21 There is also renewed interest in combined partial knee arthroplasty (CPKA) 22 , 23 where combinations of two or more partial knee arthroplasty (PKA) implants are used in the same knee. 24 Recent data have suggested that two-thirds of TKA patients could be candidates for PKA or CPKA.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to such design, it was believed that patients will have not only better functional results but also better gait pattern and lower risk of polyethylene wear. However, in several studies [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ] no superiority of this design was observed in comparison to the PS one in terms of patients’ satisfaction or improvement in range of motion. Only one study [ 21 ] reported a significantly better outcome of MP design in terms of Forgotten Joint Score.…”
Section: Introductionmentioning
confidence: 93%
“…Even though there are many studies concerning gait pattern after TKA [ [25] , [26] , [27] ], it is estimated that only one-third of patients show a biphasic pattern of sagittal plane moments which is considered physiological [ 28 ]. However, to our best knowledge, there is no study analyzing gait parameters of the knee after TKA with the use of MP knee design, and there are only two randomized-controlled trials, where authors compared gait patterns between two designs of TKA implants [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%